General rules for Peace in the Sunnah: A Collection and Study - Jalal, Ismael; Qadir, Fadhil (Islamic Sciences Journal, 2023)
The idea of the research revolves around some of the rules related to civil peace in the purified Sunnah of the Prophet, including the rule that peace is the origin in relations and war is an exception, an authentic and deep rule applied in all areas of the biography of the Prophet, peace be upon him, so that all components of society can live in peace, security and stability. Continuous constructive dialogue and stable peace are the cornerstones in the upbringing of a people and a calm society that is governed by kindness and peace. So quarrels, hatred and fighting are absent from it. By presenting the side of the spirit of peace over the side of the flames of war and devastation, and our Prophet Muhammad, peace and blessings be upon him, emphasized it with his words, deeds and daily practices. And that the principle of justice and equality is one of the basic principles that our Prophet, peace and blessings be upon him, brought to achieve and to achieve peace and security between individuals, families and society. That pushes society to anarchy and terrorism, and one of the biggest reasons for raising security and safety among people is injustice in all its forms and types. Including that the rule of good neighborliness is one of the basic rules for the establishment of a peaceful society, and for the establishment of wonderful and refined civilized values. The Prophet applied this principle in Medina and elsewhere, and the rule of moderation and moderation paves the way for peaceful civil coexistence in society through tolerance and positive interaction among all human beings.